2005
DOI: 10.1016/s0002-9440(10)62328-0
|View full text |Cite
|
Sign up to set email alerts
|

Transdifferentiation of Mature Rat Hepatocytes into Bile Duct-Like Cells in Vitro

Abstract: We investigated the mechanism of phenotypic plasticity of hepatocytes in a three-dimensional organoid culture system, in which hepatocytic spheroids were embedded within a collagen gel matrix. Hepatocytes expressed several bile duct markers including cytokeratin (CK) 19 soon after culture and underwent branching morphogenesis within the matrix in the presence of insulin and epidermal growth factor. Cultured hepatocytes did not express Delta-like, a specific marker for oval cells and hepatoblasts. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 55 publications
9
87
0
1
Order By: Relevance
“…20,21 The recovery of albumin expression in transdifferentiated hepatocytes was enhanced by Dex, which has been shown to increase albumin and TAT expression in spheroidal aggregate cultures of newborn rat hepatocytes 18 and decrease CK 19 mRNA expression in monolayer-cultured rat hepatocytes. 7 Although the mechanism of the effect of Dex on hepatocytic phenotypes has not been elucidated, this study suggests that the inhibition of the MEK and JNK signaling pathways may be important. In a previous study, we also found that PD98059 inhibited aberrant CK 19 expression in hepatocytes cultured within the collagen gel matrix.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…20,21 The recovery of albumin expression in transdifferentiated hepatocytes was enhanced by Dex, which has been shown to increase albumin and TAT expression in spheroidal aggregate cultures of newborn rat hepatocytes 18 and decrease CK 19 mRNA expression in monolayer-cultured rat hepatocytes. 7 Although the mechanism of the effect of Dex on hepatocytic phenotypes has not been elucidated, this study suggests that the inhibition of the MEK and JNK signaling pathways may be important. In a previous study, we also found that PD98059 inhibited aberrant CK 19 expression in hepatocytes cultured within the collagen gel matrix.…”
Section: Discussionmentioning
confidence: 84%
“…In situ two-step collagenase liver perfusion and cell isolation were performed as previously described. 7,8 Alb-DsRed2 rats, which express DsRed2 fluorescence under the control of the albumin enhancer/promoter, were used to monitor the level of albumin expression in hepatocytes. 15 The protocols for animal experimentation were …”
Section: Isolation Of Rat Hepatocytesmentioning
confidence: 99%
See 3 more Smart Citations